Implementasi Sabar dalam Kisah Nabi Yusuf pada Keterampilan Konselor - Habibi, Ahmad (Department of Islamic Guidance and Counseling, 2024)
Counselor skills are a counselor’s ability to provide guidance and counseling services. Skills are one of the main assets that a counselor must have because skills occupy a vital position in the counseling service process. Counselor skills are not only seen in terms of material mastery skills (intellectual) and attitudes (emotional), but the skills that have an important role that counselors must have are religious (spiritual) experience skills. One of the stories in the Qur'an that contains social-spiritual value is the story of the Prophet Yusuf a.s. The story of the Prophet Yusuf is described in a flexible manner in Surah Yusuf verse 4-101. It contains the struggle, strategy and patience of Prophet Yusuf in living his life both personally, as a family and within the wider community (social public). This type of research is qualitative library research. Meanwhile, the data analysis method used is the content analysis method. The research results illustrate the implementation of patience in the story of the Prophet Yusuf in counselor skills, namely the processes of attending, leading and following up, which are basic units that are interrelated and systematically sequential so that the counseling process is well directed KEYWORDS: Prophet Yusuf, Counselor, Patient, Al-Qur’an